KONSUMSI JAJANAN KAITANNYA DENGAN ASUPAN GULA, GARAM, LEMAK PADA REMAJA JEPARA SELAMA PANDEMI COVID-19. - Dzakiyya Sabriani Maziyah; Teddy Wahyu Nugroho; A. Fahmy Arif Tsani; Fillah Fithra Dieny (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2023)
ABSTRACTBackground: The current COVID-19 pandemic has led Indonesia’s government to impose quarantine rules on their citizens. The consequence was a change in lifestyle and eating habits that strongly supported the populace in order to consume more food.Objectives: The study was to establish the relationship between foods consumed with sugar, salt, and fat intake during covid-19 pandemic in adolescents.Methods: An analytical observational study with cross sectional design. The research was conducted by online with 84 adolescents by simple random sampling in Jepara district. Data on snack consumption habits was obtained through a questionnaire from the Google form application. Data of snack consumption habits was obtained through a questionnaire from the Google form application. Data of snack and sugar, salt, and fat intake obtained through food frequency questionnaire (FFQ). Data were analyzed by chi square.Results: All respondence had poor snack consumption habits 91.7%, with excess sugar intake 89,3%, excess salt intake 66.7%, and excess fat intake 71%. Analyzed results obtained there were relation snack consumption habits and sugar intake (p<0.001), with salt intake (p=0.002), with fatty intake (p<0.001). Conclusion: There were correlation between snack consumption habits and intake of sugar, salt and fat during the covid-19 pandemic in adolescents. Keywords: Adolescents; Covid-19; Snack consumption; Sugar intake. ABSTRAKLatar belakang: Pandemi Covid-19 menyebabkan pemerintah Indonesia menetapkan aturan karantina pada warganya. Konsekuensinya adalah perubahan gaya hidup dan kebiasaan makan yang sangat mendukung masyarakat untuk lebih banyak mengonsumsi makanan jajanan.Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan konsumsi makanan jajanan dengan asupan gula, garam, dan lemak pada saat pandemi covid-19 pada remaja.Metode: Penelitian ini merupakan penelitian observasional dengan rancangan cross sectional. Penelitian ini dilaksanakan secara online dengan metode pengambilan sampel Simple Random Sampling diperoleh 84 remaja usia 10-19 tahun di kecamatan Jepara. Data kebiasaan konsumsi jajan diperoleh melalui kuesioner dari aplikasi google form. Data konsumsi jajan dan asupan gula, garam, lemak diperoleh melalui semi quantitative food frequency questionnaire (SQ-FFQ). Analisis menggunakan uji Chi-Square.Hasil: Sebanyak 91,7% responden memiliki kebiasaan jajan yang tidak baik dengan asupan gula berlebih 89,3%, asupan garam berlebih 66,7%, dan asupan lemak berlebih 71%. Hasil uji menunjukkan terdapat hubungan antara konsumsi jajanan dengan asupan gula (p<0,001), dengan asupan garam (p=0,002), dengan asupan lemak (p<0,001).Simpulan: Terdapat hubungan antara kebiasaan konsumsi jajanan dengan asupan gula, garam, dan lemak selama pandemi covid-19 pada remaja. Kata kunci: Asupan gula; Covid-19; Konsumsi jajan; Remaja